THE EXTENT OF THE UTILIZATION OF TEACHERS ON THEIR LEARNING DERIVED FROM THE WEBINARS ATTENDED DURING THE NEW NORMAL - Gerald D. Purigay (PT. BATARI EDU CALYA, 2023)
In the competitive world that we are living in, upgrading our skills and knowledge is very much relevant. Despite pandemic restrictions, teachers still strive to adopt a new normal education through different webinar series. This study aimed to bridge the gap between the importance of different institutions' webinars and their utilization being extended by the teachers. This study used a quantitative type of research to quantify and analyze the difference between the extent of utilization of teachers on their learning derived from webinars attended during the new normal and the profile of the respondents. Respondents of this study were 30 teaching personnel from Sto. Domingo Elementary School. The result of the study showed that teachers always utilized their learning derived from the webinars they attended in teaching strategy, assessment of learning, and school operation; however, they often utilized their learning in instructional materials preparation. It also showed that there is no significant difference between the profile of the respondents and their extent of utilization of learning derived from webinars they attended.